Face-to-face intercrossed ZnO nanorod arrays with extensive NR-NR homojunctions for a highly sensitive and self-powered ultraviolet photodetector. (November 2019) - Chen, Changsong; Hu, Baofa; Wang, Zhen; Lv, Xueqin; Zhang, Chunquan; Chen, Binbin; San, Haisheng; Hofmann, Werner
Abstract: A self-powering ultraviolet photodetector (UVPD) that effectively utilizes UV energy in an easy-to-implement way is an attractive alternative for the UV optical sensing and communication. Here we report a novel self-powered UVPD based on a face-to-face hybrid ZnO nanorod arrays (ZNRAs) nanostructure. Large-area free-standing ZNRAs have been grown on indium tin oxide (ITO) conductive glass and Ti substrates through a hydrothermal method. Different geometric dimension of ZNRAs/ITO and ZNRAs/Ti structures were designed to pair hybrid each other for achieving the optimum photoelectric performance. Experimentally, it is found that the optimum UVPD based on face-to-face hybrid ITO/ l -ZNRAs/ l -ZNRAs/Ti structure exhibits an enhancement of '1+1>2' in photoelectric conversion without applying any external DC voltage when compared with single-face ZNRAs-based UVPDs, and the optimum UVPD demonstrates a responsivity of 2.45 mA W −1 and on/off current ratio of 6.6 × 10 5 under a UV irradiation of 3.06 μW cm −2 as well as a high durability with a cyclic balance of no less than 93.5% in a 4250-s on/off irradiation. The generation of self-power and the high photoelectric performance of face-to-face hybrid ZNRAs-based UVPDs are associated to the Schottky junctions in ITO/ZnO interface as well as the extensive ZnO nanorod-nanorod homojunction. Graphical abstract: Image 1 Highlights: A self-powered Ultraviolet photodetector based on a novel face-to-face hybrid ZnO nanorod arrays (ZNRAs) nanostructure is presented. The optimum face-to-face device exhibits '1+1>2' enhancement in photoelectric conversion when compared with single-face ZNRAs-based device. The ZnO/ITO Schottky junction and extensive NR-NR homojunction facilitate the self-power generation and the high photoelectric performance.